The designing of launch vehicles with liquid propulsion engines ensuring fire, explosion and environmental safety requirements of worked-off stages. (February 2017) - Trushlyakov, V.; Shatrov, Ya.; Sujmenbaev, B.; Baranov, D.
Abstract: The paper addresses the problem of the launch vehicles (LV) with main liquid propulsion engines launch technogenic impact in different environment areas. Therefore, as the study subjects were chosen the worked-off stages (WS) with unused propellant residues in tanks, the cosmodrome ecological monitoring system, the worked-off stage design and construction solutions development system and the unified system with the "WS+the cosmodrome ecological monitoring system+design and construction solutions development system" feedback allowing to form the optimal ways of the WS design and construction parameters variations for its fire and explosion hazard management in different areas of the environment. It is demonstrated that the fire hazard effects of propellant residues in WS tanks increase the ecosystem disorder level for the Vostochny cosmodrome impact area ecosystem. Applying the system analysis, the proposals on the selection of technologies, schematic and WS design and construction solutions aimed to the fire and explosion safety improvement during the LV worked-off stages with the main liquid propulsion engines operation were formulated. Among them are the following: firstly, the unused propellant residues in tanks convective gasification based on the hot gas (heat carrier) supply in WS tanks after main liquid propulsion engines cutoff is proposed as the basic technology; secondly, the obtained unused propellant residues in WS tanks gasification products (evaporated propellant residues + pressurizing agent + heat carrier) are used for WS stabilization and orientation while descending trajectory moving. The applying of the proposed technologies allows providing fire and explosion safety requirements of LV with main liquid propulsion engines practically. Highlights: The paper addresses the problem of the launch vehicles (LV) with main liquid propulsion engines launch technogenic impact in different environment areas. Therefore, as the study subjects were chosen the worked-off stages (WS) with unused propellant residues in tanks, the cosmodrome ecological monitoring system, the worked-off stage design and construction solutions development system and the unified system with the "WS+the cosmodrome ecological monitoring system+design and construction solutions development system" feedback allowing to form the optimal ways of the WS design and construction parameters variations for its fire and explosion hazard management in different areas of the environment. It is demonstrated that the fire hazard effects of propellant residues in WS tanks increase the ecosystem disorder level for the Vostochny cosmodrome impact area ecosystem. Applying the system analysis, the proposals on the selection of technologies, schematic and WS design and construction solutions aimed to the fire and explosion safety improvement during the LV worked-off stages with the main liquid propulsion engines operation were formulated. Among them are the following: firstly, the unused propellant residues in tanks convective gasification based on the hot gas (heat carrier) supply in WS tanks after main liquid propulsion engines cutoff is proposed as the basic technology; secondly, the obtained unused propellant residues in WS tanks gasification products (evaporated propellant residues+pressurizing agent+heat carrier) are used for WS stabilization and orientation while descending trajectory moving. The applying of the proposed technologies allows providing fire and explosion safety requirements of LV with main liquid propulsion engines practically. Design-and-construction implementation of the suggested technology involves the installation of the autonomous onboard de-orbiting system at the LV worked-off stages, wherein "dry" mass of this system structure does not exceed 5% from the mass of "dry" LV stage structure.